Tenure security: Why it matters - Swallow, Brent M. (International Food Policy Research Institute, 2021)
Collaborative international research on tenure dates back at least to the early 1960s when the Land Tenure Centre was established at the University of Wisconsin-Madison and conducted some studies in collaboration with CGIAR social scientists. CGIAR interest in tenure increased in the early 1990s when natural resource management was strengthened as a component of the CGIAR agenda and the Centers on forests, agroforestry, and water (CIFOR, ICRAF, and IWMI) entered the system. CAPRi began to operate as a systemwide research program on tenure and collective action in the mid-1990s, and became PIM Flagship 5 on governance of natural resources in 2011. From 2021, a renewed research agenda on tenure is essential for advancing the One CGIAR mission of “science and innovation that advance transformation of food, land and water systems in a climate crisis.”